Perbandingan Penerapan Sistem Akuntansi Konvensional dengan Sistem Akuntansi Berbasis Komputer pada Perusahaan Dagang - Uding Sastrawan; Ratih Pratiwi; Eka Merdekawati (IPB University, 2012)
The implementation of conventional accounting system is based on the accounting records which are done manually (paper work). In contrast, the implementation of computer-based accounting system is an impact of the development of science and technology. Therefore, the manually accounting records can be replaced by computersin terms of data processing of daily transactions to financial reports. The purposes of this research are firstly to determine the implementation of conventional accounting system at UD. Mekarsari. Secondly is to determine the implementation of computer-based accounting system in PD. Cimanggu Jaya. Lastly is to compare those two accounting systems which have been applied to the two companies. The difference of those two models of accounting system can be seen from the output of the accounting records. All variables or sub systems that run on those two trading companies with different accounting recording system is the study of assessment of the implementation between conventional accounting system and computer accounting systems so that two accounting systems can be compared. Last stepistoprovidere commendations for improvement in the implementation ofthe accounting system for more efficiency and effectiveness when applied in the trading companies. Based on the results and discussion, it can be summarized as follows: 1). The application of conventional accounting systems at UD. Mekar Sari is still simple. 2). The application of computer-based accounting system at PD. Cimanggu Jaya has formed separate functions, all transactions are recorded in the printed serial numbered transaction receipt, and has done journal recording to generate financial reports using computer applications ie Microsoft Office Excel. 3). The comparison between the conventional accounting system and computer-based accounting system on timber commodity trading company shows that the conventional accounting system is more simple, their functions have no optimal performance, and the application of internal control is still lacking, so the company’s financial statements has not been realized.Keyword : Accounting System,Conventional Accounting System, Computer Based Accounting System